Particle-based perception of garment folding for robotic manipulation purposes - Hou Y.C.; Mohamed Sahari K.S.; Weng L.Y.; How D.N.T.; Seki H. (SAGE Publications Inc., 2023)
Mobile robots; Object recognition; Robotics; Robots; Combined model; Deformable object; Home service robot; Polygonal modeling; Polygonal models; Recognition process; Robotic manipulation; Robotic platforms; Parameter estimation